THE EFFECT OF AUDIT TENURE AND CLIENT COMPANY SIZE ON AUDIT QUALITY - Yoelanda Asri Sitohang; Rini Susiani (SEAN Institute, 2023)
The purpose of this study is to find empirical evidence regarding the factors that influence audit quality in companies in Indonesia. The population in this study are 26 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The sample selection method used purposive sampling, with a total sample of 11 companies. The data analysis method in this study uses multiple linear regression. The results of this study prove that audit tenure has no significant effect on audit quality, and the size of the client company has a significant effect on audit quality. Simultaneously audit tenure and firm size affect audit quality.